2016
DOI: 10.1111/jcmm.13049
|View full text |Cite
|
Sign up to set email alerts
|

Matrine induces Akt/mTOR signalling inhibition‐mediated autophagy and apoptosis in acute myeloid leukaemia cells

Abstract: Pharmacological modulation of autophagy has been referred to as a promising therapeutic strategy for cancer. Matrine, a main alkaloid extracted from Sophora flavescens Ait, has antitumour activity against acute myelocytic leukaemia (AML). Whether autophagy is involved in antileukaemia activity of matrine remains unobvious. In this study, we demonstrated that matrine inhibited cell viability and colony formation via inducing apoptosis and autophagy in AML cell lines HL‐60, THP‐1 and C1498 as well as primary AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 39 publications
4
49
0
Order By: Relevance
“…After treatment with different concentrations of tigecycline with or without bafilomycin A1 (baf A1), the cells were collected and lysed immediately using RIPA lysis buffer (Beyotime Institute of Biotechnology) supplemented with PMSF and Halt protease and phosphatase inhibitor cocktail (Pierce, Rockford, IL). The protein was boiled for 8 minutes in 1× loading buffer and subjected to Western blot analysis using antibodies against SQSTM1/p62, LC3, p‐mTOR, mTOR, p‐AMPKa, AMPKa, p‐p70S6K, p70S6K, p‐4E‐BP1, 4E‐BP1 or GAPDH as reported previously . The bands were visualized by an enhanced chemiluminescence reagent (Thermo Fisher, Fremont, CA), and the optical densities of the bands were analysed using Image J software (NIH, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…After treatment with different concentrations of tigecycline with or without bafilomycin A1 (baf A1), the cells were collected and lysed immediately using RIPA lysis buffer (Beyotime Institute of Biotechnology) supplemented with PMSF and Halt protease and phosphatase inhibitor cocktail (Pierce, Rockford, IL). The protein was boiled for 8 minutes in 1× loading buffer and subjected to Western blot analysis using antibodies against SQSTM1/p62, LC3, p‐mTOR, mTOR, p‐AMPKa, AMPKa, p‐p70S6K, p70S6K, p‐4E‐BP1, 4E‐BP1 or GAPDH as reported previously . The bands were visualized by an enhanced chemiluminescence reagent (Thermo Fisher, Fremont, CA), and the optical densities of the bands were analysed using Image J software (NIH, Bethesda, MD).…”
Section: Methodsmentioning
confidence: 92%
“…The protein was boiled for 8 minutes in 1× loading buffer and subjected to Western blot analysis using antibodies against SQSTM1/p62, LC3, p-mTOR, mTOR, p-AMPKa, AMPKa, p-p70S6K, p70S6K, p-4E-BP1, 4E-BP1 or GAPDH as reported previously. 19 The bands were visualized by an enhanced chemiluminescence reagent (Thermo Fisher, Fremont, CA), and the optical densities of the bands were analysed using Image J software (NIH, Bethesda, MD). When tumour volume reached approximately 300 mm 3 , the mice were randomized into four groups.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…A portion of the cytosol is sequestered by a so‐called isolation membrane, formation of a double‐membrane structure called the autophagosome, which subsequently fuses with the lysosome/vacuole . Although physiological levels of autophagy are essential for the maintenance of cellular homeostasis during various stress conditions, excessive or uncontrolled levels of autophagy are able to induce cell death . Therefore, autophagy is a double‐edged sword, which has a protective role against cell death or contributes to autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…As a major regulator of mammalian autophagy and apoptosis, mTOR is the central processor and integrator of internal and external signals . The occurrence of autophagy and apoptosis is accompanied by the inhibition of AKT/mTOR signalling pathway . Moreover, studies have shown that muscone can induce phosphorylation of AKT during myocardial infarction in mice .…”
Section: Discussionmentioning
confidence: 99%